Usaha Kita Groups Economic Activities as a Learning Resources on Social Studies - Riski Norseli; Syaharuddin Syaharuddin; Muhammad Rezky Noor Handy; Bambang Subiyakto; Ersis Warmansyah Abbas (Universitas Lambung Mangkurat, 2023)
The lack of income for family members will affect survival. Through the economic activities of the fish cracker business group, there are aspects, such as production and distribution. Economic activities provide a place for teachers to develop the material, adding examples in the environment around where they live as social studies learning resources. This study aims to determine how the fish cracker business group conducts economic activities. This research uses a qualitative approach with descriptive methods. Data was obtained through observation, interviews, and documentation. Test the validity of the data through source, technique, and time triangulation. Data is presented in the form of descriptions and pictures. The research results are production activities, distribution, and consumption by the Usaha Kita group in Banua Anyar village. Production is carried out by several business group members, namely by processing haruan/snake fish into crackers. Distribution is done directly by selling online via WhatsApp and indirectly through intermediaries distributed to restaurants. Consumption is done directly in the restaurant. Economic activities carried out by business groups, such as distribution, production, and consumption, can be used as contextual social studies learning resource on economic activity material so that it aims for students to understand the surrounding environment and can be used as a learning resource. The existence of these activities can make it easier for teachers to provide examples and link them to learning resources on social studies.